Pollution Control in Coal Fired Thermal Power Plant Flue Gas Desulfrisation System Technology Analyis and Selection - Vidjayan, S.; Ananth Vino, V. Jose (International Journal of Psychosocial Rehabilitation, 2019)
The Fossil fuels (Coal) used in thermal power plants contain significant amounts of sulfur. At burning, about 95% of the sulfur is converted to sulfur dioxide (SO2), which reacts with the particles of water in the atmosphere, forming acid rain under normal conditions of temperature and pressure. Sulfur dioxide, through its annual emissions, is the main gas pollutant. The flue gas desulphurization can be done both by wet or dry process. The most used process is wet desulphurization of limestone or lime, accounting for about 80% of all desulphurization processes. The paper presents the current Norms technology in FGD for SOX in the world, their advantages and disadvantages analysis, as well as the future trends and selection of optimal technology